Computation on standard deviation and variation in phasal quantitative determination using X-ray diffraction - Le, Chí Cương (Journal of Technical Education Science, 2014)
This paper presents a new method for calculation the standard deviation and variation of phase quantitative determination using X-ray diffraction. The calculated results were compared to those determined from the microscopic and imaging process method, which is widely used in the industry. The strong agreement between the two methods shows the high reproducibility of the X-ray diffraction method together with the possibility of replacing the traditional microscopic method.